Codon choice and gene expression: synonymous codons differ in their ability to direct aminoacylated-transfer RNA binding to ribosomes in vitro. - Thomas, L K (1988)
Phe-tRNA (anticodon GAA)--polypeptide-chain elongation factor Tu-GTP ternary complexes react faster with ribosomes programmed with UUC codons than with ribosomes programmed with UUU codons. A similar preference is shown by Leu-tRNA2 (anticodon GAG) complexes, which react faster with ribosomes programmed with CUC than with those programmed with CUU. The difference is seen in the rate of ternary-complex binding to the ribosome; no differences are seen in peptide-bond formation. Highly expressed mRNAs in Escherichia coli favor codons terminating in cytosine rather than uracil when both codons are read by a single tRNA with an anticodon beginning with guanine. The results suggest that intrinsic differences between the efficiencies of synonymous codons play an important role in modulating gene expression in E. coli.